2012
DOI: 10.15560/8.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Variation in butterfly diversity and unique species richness along different habitats in Trishna Wildlife Sanctuary, Tripura, northeast India

Abstract: Quantification of butterfly diversity and species richness is of prime importance for evaluating the status of protected areas. Permanent line transect counts were used to record species richness and abundance of butterfly communities of different habitat types in Trishna wildlife sanctuary. A total of 1005 individuals representing 59 species in 48 genera belonging to five families were recorded in the present study. Of these, 23 species belonged to the family Nymphalidae and accounted for 38.98% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Also, the study recorded a relatively high diversity of butterfly species and species richness in PA compared to UPA [15]. The higher diversity, minimum dominance, and occurrence of 10 unique families of butterflies recorded in PA as against 8 recorded in UPA may be attributable to the vegetation complexity and multilayered canopy of the PA, which facilitate different sets of microclimates, making the habitat distinct for different butterfly species [16]. Diversity is enhanced by the presence of specialists that exhibit distinct habitat preferences [17,18].…”
Section: Discussionmentioning
confidence: 79%
“…Also, the study recorded a relatively high diversity of butterfly species and species richness in PA compared to UPA [15]. The higher diversity, minimum dominance, and occurrence of 10 unique families of butterflies recorded in PA as against 8 recorded in UPA may be attributable to the vegetation complexity and multilayered canopy of the PA, which facilitate different sets of microclimates, making the habitat distinct for different butterfly species [16]. Diversity is enhanced by the presence of specialists that exhibit distinct habitat preferences [17,18].…”
Section: Discussionmentioning
confidence: 79%
“…Several authors have been using the Bray–Curtis similarity index for cluster analysis of ecological data (Anu and Sabu, 2006; Singh, 2008; Majumder et al, 2012). It has been demonstrated that the analysis using Bray–Curtis distances (Bray and Curtis, 1957) is an appropriate tool for the evaluation of the discrimination of insect species using hydrocarbon profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Troideshelena was found in Velodrom. This species is one of worldwide protected species [8], so their habitat (Velodrom) needs to be conserved in order to support their life.…”
Section: Resultsmentioning
confidence: 99%